Keselamatan Oleh Iman Berdasarkan Surat Roma - William Hermon Beltsazar Dongoran (Angelion, 2021)
Salvation by faith is a theological topic that is still being discussed and debated among theologians. The classical debate between Calvinism and Arminianism is still developing from both the point of view of dogmatics and systematic theology. Because the differences that exist make the understanding of salvation also different. In the discussion about salvation often the discussion does not go well, because each stick to the concept of salvation based on dogma. In understanding the systematic theology related to salvation is also influenced by dogma and ignores elements of biblical theology, the concept of salvation by faith written by Paul needs to be reexamined, considering that Paul's Theology is very sharp in reviewing the Theology of Salvation by Faith in Romans. It is very interesting that the line of thought in Romans which can be examined especially regarding salvation by faith. So seeking the truth about salvation by faith in Rome is not a regression in theology. In fact, examining Romans is a very basic step in seeking the truth about salvation by faith. The problem in this research is to find an understanding of salvation by faith based on Romans and what dimensions are in Romans that become the flow of thinking in discussing salvation by faith. The conclusion of this research. The author finds that Paul is very consistent in making God's righteousness the main concept in understanding salvation by faith. And consistency makes God's righteousness the center of the development of salvation by faith into something that is always new.Keselamatan oleh iman adalah merupakan topik teologi yang masih terus dibicarakan dan diperdebatkan di kalangan para teolog. Perdebatan klasik antara Calvinisme dan Arminianisme masih terus berkembang baik dari sudut dogmatika dan juga Teologi Sistimatika. Karena perbedaan yang ada membuat pemahaman tentang keselamatan juga berbeda. Dalam diskusi tentang keselamatan seringkali diskusi menjadi tidak berjalan dengan baik, karena masing-masing bertahan dengan konsep keselamatan yang berdasarkan dogma. Dalam memahami Teologi Sistimatika yang berkaitan dengan keselamatan juga dipengaruhi oleh dogma dan mengabaikan unsur Teologi biblika, Konsep Keselamatan Oleh Iman yang ditulis oleh Paulus perlu dikaji kembali, mengingat Teologi Paulus sangat tajam sekali dalam mengulas Teologi Keselamatan Oleh Iman dalam Surat Roma. Sangat menarik sekali alur berpikir dalam Surat Roma yang dapat diteliti khususnya mengenai keselamatan oleh iman. Sehingga mencari kebenaran tentang keselamatan oleh iman dalam Roma bukanlah sebuah kemunduran di dalam berteologi. Justru meneliti surat Roma adalah langkah yang sangat mendasar dalam mencari kebenaran tentang keselamatan oleh iman. Masalah dalam penelitian ini adalah untuk mencari pengertian mengenai keselamatan oleh iman berdasarkan Surat Roma dan dimensi apa saja yang ada dalam surat Roma yang menjadi alur berpikir dalam membahas keselamatan oleh iman. Kesimpulan dari penelitian ini Penulis menemukan bahwa Paulus sangat konsisten untuk menjadikan kebenaran Allah menjadi konsep utama dalam memahami keselamatan oleh iman.Dan konsistensi menjadikan kebenaran Alllah menjadi pusat dari pengembangan keselamatan oleh iman menjadi sesuatu yang selalu baru.